Thursday
March 23, 2017

Post a New Question

Posted by on Friday, September 28, 2007 at 11:06pm.

I solved this problem
12x-6=11x
-6+6=0 11x+6
12x=11x+6
12x-11x=x 11x-11x=0 x=6

Can someone show me the process of checking it?

  • math - , Friday, September 28, 2007 at 11:12pm

    Substitute your answer of x = 6 for x in the original problem. Like so:
    12(6) - 6 = 11(6)
    72 - 6 = 66
    66 = 66

  • math - , Saturday, September 29, 2007 at 1:29am

    thank you

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question